Ketoprofen pharmacokinetics of R‐ and S‐isomers in juvenile loggerhead sea turtles (Caretta caretta) after single intravenous and single‐ and multidose intramuscular administration. Issue 2 (22nd October 2017) - Thompson, K. A.; Papich, M. G.; Higgins, B.; Flanagan, J.; Christiansen, E. F.; Harms, C. A.
Abstract : Ketoprofen is a nonsteroidal anti‐inflammatory and analgesic agent that nonselectively inhibits cyclooxygenase, with both COX‐1 and COX‐2 inhibition. Recent studies on COX receptor expression in reptiles suggest that nonselective COX inhibitors may be more appropriate than more selective inhibitors in some reptiles, but few pharmacokinetic studies are available. The goal of this study was to determine single‐ and multidose (three consecutive days) pharmacokinetics of racemic ketoprofen administered intravenously and intramuscularly at 2 mg/kg in healthy juvenile loggerhead turtles ( Caretta caretta ). The S ‐isomer is the predominant isomer in loggerhead sea turtles, similar to most mammals, despite administration of a 50:50 racemic mixture. Multidose ketoprofen administration demonstrated no bioaccumulation; therefore, once‐daily dosing will not require dose adjustment over time. S ‐isomer pharmacokinetic parameters determined in this study were C max of 10.1 μg/ml by IM injection, C 0 of 13.4 μg/ml by IV injection, AUC of 44.7 or 69.4 μg*hr/ml by IM or IV injection, respectively, and T ½ of 2.8 or 3.6 hr by IM or IV injection, respectively. Total ketoprofen plasma concentrations were maintained for at least 12 hr above concentrations determined to be effective for rats and humans. A dose of 2 mg/kg either IM or IV every 24 hr is likely appropriate for loggerhead turtles.